Bilateral investment treaties’ protection for multinational companies - Elfakharani, Ashraf M. A.; Abdul Rahman, Rohana; Abdullah, Nor Anita (2016)
Bilateral investment treaties (BITs) provide conditional terms which regulate investments between two countries, and are used as a tool for economic growth by attracting external investments.However, some countries claim BITs are a threat to economic and social policies. Furthermore, BITs play a role as a legal cover for unconditional protection for Multinational Companies (MNCs), without linking the terms of protection to any party on the MNCs side.Thus, no provisions deal with acts or the very idea of corruption, or refer to the state’s right to safeguard public money and maintaining sovereignty, which become overruled under international arbitration. With a broad definition for “investor,” the question of who gets protection under the treaty is not strictly answered.Upon signing a treaty, the investors (signing party) already present in a country (with whom their state signed a BIT), and potential future investors, become protected under the terms of the treaty.This article addresses the very question on whether BITs are a safe haven for encroachments by MNCs, through literature review and various cases that exhibit abuse of BITs in the respective host state.This article provides an understanding as to why BITs are considered a safe haven for the MNCs